Cognitive Dysfunction in Multiple Sclerosis - Guimarães, Joana; Sá, Maria José (Frontiers in Neurology, 2012)
In Multiple Sclerosis (MS) prevalence studies of community and clinical samples, indicate that 45–60% of patients are cognitively impaired. These cognitive dysfunctions have been traditionally described as heterogeneous, but more recent studies suggest that there is a specific pattern of MS-related cognitive dysfunctions. With the advent of disease-modifying medications for MS and emphasis on early intervention and treatment, detection of cognitive impairment at its earliest stage becomes particularly important. In this review the authors address: the cognitive domains most commonly impaired in MS (memory, attention, executive functions, speed of information processing and visual spatial abilities); the physiopathological mechanism implied in MS cognitive dysfunction and correlated brain MRI features; the importance of neuropsychological assessment of MS patients in different stages of the disease and the influence of its course on cognitive performance; the most used tests and batteries for neuropsychological assessment; therapeutic strategies to improve cognitive abilities.